2015
DOI: 10.1007/s40825-015-0018-7
|View full text |Cite
|
Sign up to set email alerts
|

Emission Reduction with Diesel Particle Filter with SCR Coating (SDPF)

Abstract: The present paper informs about some results obtained with selective catalytic reduction (SCR) and with SDPF (a diesel particle filter (DPF) with SCR coating) on a medium duty research engine Iveco F1C. This work is a first attempt at evaluating the effects of a SDPF on non-legislated gaseous emissions and on secondary nanoparticles. Beside the limited gaseous emission components, NH 3 , NO 2 , and N 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 23 publications
(35 reference statements)
2
8
0
Order By: Relevance
“…Urea overdosing did not further increase the concentration of particles being formed with stoichiometric dosing. This is in agreement with what Czerwinski et al (2015) observed in tests of a combined SCR DPF system. Similarly, Robinson et al (2016) reported a minor effect in regulated PN emissions when shifting from 1.1 to 1.5 ANR.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Urea overdosing did not further increase the concentration of particles being formed with stoichiometric dosing. This is in agreement with what Czerwinski et al (2015) observed in tests of a combined SCR DPF system. Similarly, Robinson et al (2016) reported a minor effect in regulated PN emissions when shifting from 1.1 to 1.5 ANR.…”
Section: Discussionsupporting
confidence: 92%
“…Such low concentrations should be available even at stoichiometric dosing employed owing to the finite conversion efficiencies of the SCR (90%-95% in the HDE tests) and also due to nonhomogeneous mixing of the injected urea. The assumption of gas-phase particle precursors is also supported from the marginal effect of overdosing on the distribution and concentration of the produced particles observed in the present and previous (Czerwinski et al 2015;Robinson et al 2016) studies. It would be expected that overdosing of urea would promote particle formation originating from impurities of urea decomposition.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The size of the particles forming in the SCR is ideal for filtration on DPFs. Accordingly, combined SCR/DPF systems or after-treatment configurations employing the SCR upstream of the DPF will efficiently capture these particles [44].…”
Section: Discussionmentioning
confidence: 99%